(untitled) (Journal of Hama University, 2022)
Coccidiosis in chickens is one of the most common and widespread diseases of poultry. Coccidiosis can lead to serious economic losses due to elevated morbidity and mortality and low feed conversion ratio as a result of inflammation and damages to the intestinal mucosa. E. acervulina is one type of Eimeria diseases in broiler chickens, which usually causes subclinical infection. While E. tenella is one of the most economically important diseases in broiler chickens which causes hemorrhage in the cecum. In order to study the production performance, an experimental trail was designed where broilers were divided into three groups of 50 1-day-old chicks and raised up to 42 days. The production efficiency post challenge with Eimeria acervulina and E. tenella was studied by calculation of both FCR and EPEF for the three experiment groups, It was proved that the E. acervulina and E.tenella infection caused significant decrease in feed intake and consequently in body weight gain, and an increase in the values ​​of (FCR), This highlights a detrimental effect on the performance parameters of broiler chickens. The FCR in the E. acervulina group was 1.866 and in the E. tenella group was 1.787, with significant difference between these E. acervulina and control group (P<0.05). When comparing the european production efficiency factor between both infected and control group the EPEF was 365.588 in control group , 226.25 in E.acervulina and 224.371 in E. tenella group, with significant differences between both infected group and control group (P<0.05). These findings could be used to further elucidate the serious damage to the host health caused by species of Eimeria infections